The Influence of Cholesterol on Membrane Targeted Bioactive Peptides: Modulating Peptide Activity Through Changes in Bilayer Biophysical Properties - Juan M. Giraldo-Lorza; Chad Leidy; Marcela Manrique-Moreno (Membranes, 2024)
Cholesterol is a biological molecule that is essential for cellular life. It has unique features in terms of molecular structure and function, and plays an important role in determining the structure and properties of cell membranes. One of the most recognized functions of cholesterol is its ability to increase the level of lipid packing and rigidity of biological membranes while maintaining high levels of lateral mobility of the bulk lipids, which is necessary to sustain biochemical signaling events. There is increased interest in designing bioactive peptides that can act as effective antimicrobial agents without causing harm to human cells. For this reason, it becomes relevant to understand how cholesterol can affect the interaction between bioactive peptides and lipid membranes, in particular by modulating the peptides’ ability to penetrate and disrupt the membranes through these changes in membrane rigidity. Here we discuss cholesterol and its role in modulating lipid bilayer properties and discuss recent evidence showing how cholesterol modulates bioactive peptides to different degrees.